PENINGKATAN LITERASI JARINGAN DAN TRANSFER DATA OFFLINE (P2P) MELALUI PELATIHAN NEARBY SHARE PADA GURU SEKOLAH DASAR DAARUL QUR'AN INTERNASIONAL - Haryono, Wasis; Rusyda Maulida; Tita Puspitasari (JAMAIKA: JURNAL ABDI MASYARAKAT, 2025)
The digital era of 2025 necessitates a fundamental transformation in teacher competencies, shifting their role from mere information providers to technology-integrated learning facilitators. However, at the operational level, many educators continue to face challenges regarding efficiency and data security, characterized by a persistent reliance on physical transfer media, such as USB flash drives, which are inherently slow and susceptible to malware. This Community Service (PkM) initiative was conducted at SD Daarul Qur'an International with the objectives of:  augmenting teachers' conceptual understanding of computer networking foundations; and providing practical skills in wireless data sharing as a swift, secure, and efficient data transfer solution independent of internet connectivity. The program, held from October 17–19, 2025, engaged 30 teachers through an andragogical approach utilizing the Gradual Release of Responsibility framework ("I Do, We Do, You Do"), encompassing lectures, demonstrations, and guided practice. Evaluative outcomes based on the Kirkpatrick Model demonstrated significant success at Level 1 (Reaction) and Level 2 (Learning). Participants exhibited high levels of engagement (average satisfaction score of 4.85/5.0) and achieved mastery of the taught skills, with 96.7% of participants successfully performing autonomous wireless data transfers by the conclusion of the session. This success was driven by the high relevance of the material to daily pedagogical workflows and the effectiveness of a training methodology that fostered professional self-efficacy. This initiative successfully enhanced teacher workflow efficiency and mitigated cybersecurity risks within the school environment. Keywords: Digital Competence for Teachers, Computer Networking, Peer-to-Peer (P2P), Wireless Data